2012
DOI: 10.1029/2011rs004753
|View full text |Cite
|
Sign up to set email alerts
|

An optimal design of a cylindrical polarimetric phased array radar for weather sensing

Abstract: [1] An optimal design of a cylindrical polarimetric phased array radar (CPPAR) for weather sensing is presented. A recently introduced invasive weed optimization (IWO) technique is employed to obtain the desired radiation pattern of the CPPAR. Instead of optimizing each element excitation in a large array (with expensive calculation costs), the modified Bernstein polynomial distribution, defined by seven parameters, is used to optimize the current distribution for the CPPAR. The simulation results show that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Although the CPPAR has several advantages compared to PPPAR, there is a concern as how to achieve the desired performance for a given antenna size. Some recent studies have shown that CPPAR is arguably best suited for fast weather surveillance with dualpolarization capability [3,4]; however, additional studies are needed to prove the polarimetric performance of this antenna. The Advanced Radar Research Center (ARRC) at the University of Oklahoma is constructing a cylindrical polarimetric phased array radar (CPPAR) demonstrator to prove the CPPAR concept through weather measurements.…”
Section: Introductionmentioning
confidence: 99%
“…Although the CPPAR has several advantages compared to PPPAR, there is a concern as how to achieve the desired performance for a given antenna size. Some recent studies have shown that CPPAR is arguably best suited for fast weather surveillance with dualpolarization capability [3,4]; however, additional studies are needed to prove the polarimetric performance of this antenna. The Advanced Radar Research Center (ARRC) at the University of Oklahoma is constructing a cylindrical polarimetric phased array radar (CPPAR) demonstrator to prove the CPPAR concept through weather measurements.…”
Section: Introductionmentioning
confidence: 99%
“…With a four-planar-faces architecture (henceforth called PPAR – planar phased array radar, from [14]), the electronic scanning has to be greater than the absolute minimum of ±45° (up to ±60 or 70° in some practical cases) for the continuity of tracks. The gain losses and the beam broadening of a four faces PPAR have been evaluated in [14, 15] versus the equivalent, cylindrical architecture (called CPAR (cylindrical phased array radar)) in the field of studies of a long-range, ground-based multifunction radar for weather and civil aircraft surveillance. The beam broadening of a planar array with respect to the operation at boresight can be compensated by an increase of the horizontal dimension of the antenna in order not to exceed the maximum main lobe width even at a 45° scan, because the azimuth resolution ( and accuracy ) requirements have to be satisfied at all scan positions.…”
Section: Comparison D-radar Versus a Fixed-faces Mfar And Antenna Secmentioning
confidence: 99%
“…Therefore, cylindrical arrays can be a good candidate. Cylindrical arrays were studied in [4,5] for fast electronic beam scanning and their benefit over planar phased arrays for the weather sensing was demonstrated. Recently, a network of sensors consisting of hundreds of small radars has been suggested to predict the meteorological phenomena properly [6].…”
Section: Introductionmentioning
confidence: 99%